Faktor-Faktor yang Berhubungan dengan Pemanfaatan Posyandu oleh Lansia di Desa Campagaya di Wilayah UPTD Galesong Kabupaten Takalar - Fitriani Fitriani; Nurekawati Nurekawati (Maternal & Neonatal Health Journal, 2021)
Posyandu for elderly people in a certain area that has been agreed upon, which is driven by the community where they can get health service. This study aims to determine the relationship between social support, attitudes and roles of cadres on the use of Posyandu in Campagaya Village in the working area of UPTD Galesong, Takalar Regency. The research design used an observational analytic design with a cross sectional approach. The population is all elderly in the village of Campagaya in the working area of UPTD Galesong, Takalar, amounting to 119 people. A total sample of 54 respondents who fall into the inclusion criteria. The independent variables are social support, attitudes and roles of cadres. The dependent variable is the use of Posyandu. Data were collected using a questionnaire and observation with a significance level of <0.05. The results showed that the relationship between social support for the elderly (? = 0.033), the relationship between family attitudes and the use of Posyandu (? = 0.001), the relationship between the role of cadres and the use of Posyandu (? = 0.000).